Pete the cat and the cool caterpillar - Dean, James, 1957- (New York: Harper, 2018)
Pete the Cat finds a caterpillar, which becomes a butterfly.
1.6
K-3
Keywords: Pete, -- the Cat (Fictitious character) -- Juvenile fiction; Cats -- Juvenile fiction; Butterflies -- Life cycles -- Juvenile fiction; Pete, -- the Cat (Fictitious character) -- Fiction; Cats -- Fiction; Butterflies -- Life cycles -- Fiction